2017
DOI: 10.23939/chcht11.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The New 1,2,3-Triazolylantracene-9,10-Diones: Synthesis and ComputerBioactivity Screening

Abstract: Abstract. 1 The reactions of 1,4(1,5)-diazido-9,10-anthracenediones with phenylacetylene and methyl propiolate under copper(I)-catalyzed reaction of the azidealkyne cycloaddition conditions have been studied and a series of new 1,2,3-triazole derivatives of 9,10-anthracendione have been obtained. The computer screening of synthesized compounds was carried out using the PASS Online software to identify areas of experimental biomedical researches. Compounds with high affinity to the receptors family of tyrosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The behavior of the azides of 9,10-anthracenedione 50, 51 in the reaction of Cucatalyzed 1,3-dipolar cycloaddition (CuAAC) with a number of substituted alkynes was investigated [31]. It was found that the use of systems such as CuI-L-proline in DMSO, CuSO 4 -potassium ascorbate in a mixture of DMF-H 2 O and CuI-TEA in chloroform led to a positive result with obtaining 1,2,3-triazole derivatives 52 only in the case of the latter option [31].…”
Section: Reactions Of Dediazonization Of 910-anthracenyl Diazonium Saltsmentioning
confidence: 99%
“…The behavior of the azides of 9,10-anthracenedione 50, 51 in the reaction of Cucatalyzed 1,3-dipolar cycloaddition (CuAAC) with a number of substituted alkynes was investigated [31]. It was found that the use of systems such as CuI-L-proline in DMSO, CuSO 4 -potassium ascorbate in a mixture of DMF-H 2 O and CuI-TEA in chloroform led to a positive result with obtaining 1,2,3-triazole derivatives 52 only in the case of the latter option [31].…”
Section: Reactions Of Dediazonization Of 910-anthracenyl Diazonium Saltsmentioning
confidence: 99%
“…The use of such well-known methods as infrared spectroscopy and X-ray powder diffraction is a powerful and indicative tool for pharmaceutical analysis. 1 The study of compounds by the method of absorption spectrophotometry in the infrared region is widely used to identify various classes of substances, determining the structure of individual molecules [2][3][4][5][6][7][8] and the composition of molecular mixtures in industrial and scientific laboratories. 9 Moreover, IR-Fourier spectroscopy makes it possible to understand better the kinetics, mechanisms, and pathways of chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, compounds with antithrombotic and antioxidant actions were found among biologically active derivatives of 9,10-anthracenedione [14][15][16][17][18]. The recent results of the successful functionalization of amino derivatives of 9,10-anthracenediones are shown in the works [16][17][18][19][20][21][22][23][24]. It is the prompts to develop this direction.…”
Section: Introductionmentioning
confidence: 99%